1983
DOI: 10.1136/gut.24.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary protein manipulation in subclinical portal-systemic encephalopathy.

Abstract: SUMMARY Eight stable cirrhotic patients with mild or subclinical portal-systemic encephalopathy (PSE) were studied after shunt surgery when they were off all antiencephalopathic therapy. Equal amounts of mixed proteins were alternated with animal or vegetable protein in a crossover protocol under metabolic conditions for five consecutive, one week periods. The different dietary periods were not associated with either a change in the neurological impairment score or the Trailmaking Tests, which showed a learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…Several lines of evidence suggest that the pathogenesis of MHE is similar to that of overt HE. [15][16][17] Several treatment modalities that reduce ammonia level have been tried in order to treat this condition, for example, dietary protein manipulation, 18 branched-chain amino acids, 19 L-ornithine L-aspartate, 20 lactulose, 21,22,46 and probiotics. 23 Most of the studies of these treatment modalities have found improvement in psychometry, [19][20][21][22][23] ammonia level, 20,23,24 and cerebral edema.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of evidence suggest that the pathogenesis of MHE is similar to that of overt HE. [15][16][17] Several treatment modalities that reduce ammonia level have been tried in order to treat this condition, for example, dietary protein manipulation, 18 branched-chain amino acids, 19 L-ornithine L-aspartate, 20 lactulose, 21,22,46 and probiotics. 23 Most of the studies of these treatment modalities have found improvement in psychometry, [19][20][21][22][23] ammonia level, 20,23,24 and cerebral edema.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Therapeutic interventions that aim to reduce ammonia are also useful in this setting. [18][19][20][21][22][23][24] Most studies have shown improvement in psychomotor functions coupled with a reduction in ammonia level. Improvement in cognitive functions may translate into improvement in HRQOL.…”
mentioning
confidence: 99%
“…In a short-term bed rest study, healthy older men were given a protein supplement of 20 g after breakfast and before sleep versus no supplement. Results movements, EEG improvements, a trend toward positive nitrogen balance, improved branched-chain amino acid to aromatic amino acid ratio, lower urine nitrogen concentrations, and lower plasma ammonia levels [36,37,41,[52][53][54] . One of the studies showed no significant differences in grade of HE, nitrogen balance, or plasma amino acids [55] .…”
Section: Timing Of Protein Supplementationmentioning
confidence: 96%
“…To date, only 7 studies have been completed that examined vegetable protein versus animal protein and their effects on hepatic encephalopathy [36,37,41,[52][53][54][55] . Six of the studies showed positive results on vegetable protein, including improved HE, improved mental status, larger bowel across daily meals, whereas frail and prefrail individuals tend to skew their protein intake toward noon meal while consuming significantly less at other meals [61] .…”
Section: Vegetable Versus Animal Protein As a Treatment And Preventiomentioning
confidence: 99%
“…Vegetable protein diets were in troduced originally with the idea that they might be useful in the treatment of hepatic encephalopathy because of variations in their amino acid composition [9]. Except for one negative study [42], vegetable protein diets have been shown to improve hepatic encepha lopathy when compared to equinitrogenous meat protein diets [9,[43][44][45], In addition to Bacterial Metabolism of Lactulose Dig Dis 1996; 14<suppl l): [53][54][55][56][57][58][59][60][61][62][63]an altered amino acid content, vegetable pro tein diets also contain from 4-to 5-fold more fiber than standard animal protein diets. The soluble metabolizable fiber component of these diets that is metabolized by the colonic microflora could increase their growth and nitrogen incorporation [26].…”
Section: Dietary Fibermentioning
confidence: 99%